A Rare Case of Acute Postrenal Failure after Prostate Surgery - Degraeve, Amandine; Tilmans, Gilles; Lorge, Francis; Dossin, Christophe; Krings, Guillaume; Gregorio, Marcello Di; Dester, Gilles Adans; Damme, Julien Van (Archives of Clinical and Medical Case Reports, 2021)
In patients with acute ureteral obstruction, rapid increase in ureteral pressure results in dilatation of the ureter and intrarenal collecting system that usually may cause renal colic. Computed tomography and ultrasound are the gold standard to evaluate uretero-hydronephrosis. We report a case of a patient who underwent a robot-assisted radical prostatectomy for cancer and developed anuria in the immediate postoperative course without pain or hydronephrosis. Clinical and conventional imaging can be normal in case of acute post-renal failure.